Anti-inflammatory effects of Frondanol, a nutraceutical extract from Cucumaria frondosa, via modulation of NF-κB and MAPK pathways in LPS-induced RAW 264.7 cells - Ghelani, Hardik; Hanspal, Kerat; Talo, Lana; Talo, Sami; Altaher, Hala; Sarsour, Hadil; Tabbal, Marah; Badawi, Sally; Collin, Peter; Adrian, Thomas E.; Jan, Reem K. (Frontiers in Pharmacology, 2025)
IntroductionFrondanol, a non-polar lipid extract derived from the edible sea cucumber Cucumaria frondosa, has shown promising anti-inflammatory properties.MethodsThis study investigated its molecular mechanisms in modulating inflammation using lipopolysaccharide (LPS)-stimulated RAW 264.7 murine macrophages.ResultsFrondanol was found to be non-cytotoxic at the tested dilutions (1:80,000 to 1:10,000). Co-treatment with LPS and Frondanol significantly reduced the production of inflammatory mediators. Nitric oxide (NO) levels were decreased by up to 30% (p < 0.05), while iNOS protein and mRNA expression were reduced by approximately 45% (p < 0.05) and 80% (p < 0.0001), respectively, at a 1:10 K dilution. Prostaglandin E2 (PGE2) levels were suppressed by nearly 40% (p < 0.0001), accompanied by a 60% reduction in COX-2 protein (p < 0.01) and a 70% decrease in COX-2 mRNA expression (p < 0.05). The pro-inflammatory cytokines including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and interleukin (IL)-6 were also significantly attenuated by Frondanol treatment. Mechanistically, Frondanol inhibited LPS-induced NF-κB activation by reducing IκBα phosphorylation and preventing nuclear translocation of NF-κB p65. Furthermore, Frondanol significantly downregulated the phosphorylation of mitogen-activated protein kinases (MAPKs), including ERK1/2, JNK, and p38.ConclusionThese results suggest that Frondanol exerts its anti-inflammatory effects through suppression of both NF-κB and MAPK signalling pathways, leading to reduced production of inflammatory mediators and cytokines. Given its efficacy and lack of cytotoxicity, Frondanol may hold strong potential as a nutraceutical agent for the prevention and management of chronic inflammatory diseases.